Oral and maxillofacial injuries in preschool children: a study in a hospital in southern Brazil (Revista da Faculdade de Odontologia - UPF, 2017)
Objective: Oral and maxillofacial (OMF) injuries in children may lead to developmental and functional disorders. In this cross-sectional study, we analyzed the pattern of OMF injuries in preschool children admitted to the emergency department of a hospital in southern Brazil. Subjects and method: We retrospectively reviewed the medical records of 1,533 patients admitted from January to December 2011 to identify children aged 0 to 5 years with a diagnosis of OMF trauma. Data were collected on demographic, seasonal and clinical variables. Results: The sample consisted of 288 preschool children (aged 0-5 years) with OMF injuries. Of these, 61.1% were male and 53.2% were < 3 years of age. Most children (84.8%) received first medical care from an dentist. Isolated facial injuries were the most common type of injury (85.1%) in this age group. Soft tissue injuries were the most common injury outcome (77.9%), occurring mainly in the nose and lips. Random accidents were the most common cause of OMF trauma (87.7%), and injuries due to falls occurred in 85.9% of these cases. The most common dental trauma was tooth displacement (69.6%). Conclusion: In conclusion, our findings indicate a higher prevalence of OMF injuries in soft tissues, especially in boys in the first three years of life. Falls were the leading cause of injury. Information related to OMF injuries in children are essential for the control of accidents and development of public health policies.